2017
DOI: 10.1002/cjce.22924
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and in vitro evaluation of hydrophobic‐modified montmorillonite stabilized pickering emulsion for overdose acetaminophen removal

Abstract: Pickering emulsion stabilized with hydrophobic‐modified montmorillonite (HMMT) was proposed for treating acute overdose acetaminophen intoxication, with a rapid removal rate, better stability, and good biocompatibility. The tiny HMMT was able to adsorb at the oil‐water interface of the Pickering emulsion to reduce the interfacial energy along with the formation of solid particle layer, in order to enhance the stability of the emulsion and improve the removal performance. With a fast removal rate, the detoxifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…In a recent study, hydrophobisation of MMT through modification with di-octadecyl dimethyl ammonium chloride was used to produce Pickering emulsions for the acute oral paracetamol intoxication treatment. In this case, hydrophobic MMT particles both stabilized the detoxifying emulsion and increased the adsorption of paracetamol [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, hydrophobisation of MMT through modification with di-octadecyl dimethyl ammonium chloride was used to produce Pickering emulsions for the acute oral paracetamol intoxication treatment. In this case, hydrophobic MMT particles both stabilized the detoxifying emulsion and increased the adsorption of paracetamol [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this work was to study the efficiency of removing carbamazepine, ibuprofen, and paracetamol from water using pristine and hydrophobic (trimethyl stearyl ammonium-modified) montmorillonite as adsorbents. The search for new potent adsorbents for these three wide-spread pharmaceuticals is important not only for wastewater decontamination but also for designing detoxification agents to treat medicine overdoses, as was recently proposed in [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its hydrophobic nature, the adsorption of SiO 2 nanoparticles at the styrene/water interphase during the o/w emulsion polymerization may be unfavorable in terms of thermodynamics, more appropriately reside in oil phase . The emulsion stability refers to the ability of an emulsion to keep its thermodynamic appearance during a certain period . Binks et al reported that the o/w emulsion using SiO 2 nanoparticles as stabilizer at all pH values with and without ion strength (NaCl) were unstable and led to creaming after 30 min .…”
Section: Resultsmentioning
confidence: 99%
“…When the volume ratio was decreased, the relative movements of inner droplets became more and more difficult, resulting in much more viscous emulsion. The inner droplets became relatively smaller and more uniform, indicating a much more stable emulsion .…”
Section: Resultsmentioning
confidence: 99%
“…State evaluation has been developed as an effective means for evaluating the operating performance of industrial processes in recent years. [1][2][3][4][5] A performancesimilarity based online operating performance evaluation method is proposed to pursue the optimal comprehensive economic benefit. [6] Based on a performance-relevant kernel independent component analysis method, a novel operating performance evaluation method is investigated, which accounts for the comprehensive economic index.…”
Section: Introductionmentioning
confidence: 99%